Kingdom of Lesotho Public Expenditure Review : Improving Expenditure Efficiency for Inclusive Development and Growth - World Bank (World Bank, Washington, DC, 2018)
This Public Expenditure Review (PER) was prepared in response to a request from the Ministry of Finance (MoF) and is designed to inform Lesotho’s fiscal consolidation due to a narrowing of its fiscal space. Lesotho is facing a tough macro-fiscal outlook due to a sharp decline in Southern African Customs Union (SACU) revenues. This situation necessitates a significant adjustment in the current fiscal stance to ensure longer-term fiscal sustainability. However, the adjustment should be tailored to minimize any adverse growth and poverty impacts. Thus, this PER is intended to support the government’s efforts to adjust its policies to better address Lesotho’s current macro-fiscal circumstances. Lesotho is one of the poorest and most unequal countries in the world, despite a relatively good growth performance over the past 15 years. Lesotho’s per capita gross national income is about 1550 US dollars. Lesotho’s poverty rate is 59 percent (1.90 US dollars purchasing power parity [PPP] per day), its Gini coefficient is 0.541, and about 59 percent of the population now lives below the international poverty line of 1.90 dollar/day. Both poverty and extreme poverty disproportionately affect the rural population, and the bottom 40 percent of Lesotho’s population experienced a decline in consumption each year between 2002 and 2011. This compares to increases, albeit meager, for the remaining 60 percent of the population over the same period. Lesotho’s gross domestic product (GDP) grew at an annual average rate of 4 percent between 2000 and 2016, whereas its GDP per capita grew at an average rate of 2.8 percent during the same period. Despite the high level of government spending, Lesotho faces challenges in addressing inclusive growth and providing access to quality services for the poor, while also operating in a highly fragile environment. After political turmoil, the new government with a fragile coalition of 7 parties was established in June 2017. The government is facing a significant challenge to improving access to and the quality of public services. It is also seeking to invigorate the domestic private sector to diversify the growth sources of its economy. The level of unemployment is very high, with a low employment-to working-age population ratio, which limits prospects for social mobility and poverty reduction.